Pendampingan Pembuatan Kerupuk Ikan Tongkol sebagai Strategi Optimalisasi Pendapatan Berkelanjutan Masyarakat Pesisir Desa Katialada Kabupaten Gorontalo Utara - Usman Usman (Universitas Negeri Gorontalo, 2026)
Fishery product processing is one of the strategic approaches to increasing the added value of fishery commodities while strengthening the economic resilience of coastal communities. As one of the main fishery commodities, mackerel tuna (Euthynnus affinis) has considerable potential to be processed into value-added food products, including fish crackers. This study aimed to produce high-quality mackerel tuna crackers and to analyze the production process and production costs as an alternative for developing fishery-based small-scale enterprises. The methods employed included the preparation of tools and materials, cleaning and grinding the fish meat, mixing the ingredients, shaping the dough, frying, packaging, direct observation of the production process, and production cost analysis. The results showed that the mackerel tuna crackers had a uniform stick shape, an attractive golden-brown color, a savory taste, a distinctive fish aroma, and a crispy texture, indicating that the product is suitable for consumption and has promising market potential. The total production cost for one production cycle was IDR 116,000, suggesting that the business can be established with relatively affordable capital. In addition to increasing the added value of fishery products, processing mackerel tuna into crackers can extend product shelf life, create new business opportunities, and improve the income of coastal communities. Therefore, the development of mackerel tuna cracker enterprises should be supported through capacity building, the adoption of improved processing technologies, innovative packaging, and strengthened business management to enhance product competitiveness and promote sustainable community economic empowerment.